High Efficiency Dual-Band Dual-Circularly Polarized Transmitarray Antenna - Tianling Zhang; Boxiang Yang; Jiayin Guo; Yuanjun Shen; Liangqin Luo; Lei Chen (Micromachines)
A dual-band dual-circularly polarized transmitarray antenna (TA) operating in the 28/39 GHz millimeter-wave band is proposed in this article. The TA unit consists of two parts: a broadband linearly polarized (LP) receiving part and a dual-band dual-circularly polarized transmitting part. An over-2-bit phase compensation is achieved by changing the size of the U-shaped slot and the rotation status of the receiving part. A 24 × 24 TA model with an aperture size of 88.8 mm × 88.8 mm is built up by using the proposed units and fed by a wide-band corrugated horn antenna. The simulated results show that the maximum gain of the dual-band dual-circularly polarized TA is 26.28 dBic within the low-band (26.5–29.5 GHz) and 27.4 dBic within the high-band (37–40 GHz). To verify the accuracy of the simulation, a prototype of the proposed TA is fabricated and measured. The measured maximum efficiencies are 53.56% and 42.89% in low and high bands, respectively. The proposed TA covers two bands (28/39 GHz) for fifth generation (5G) millimeter-wave applications. Moreover, it features low cost, high gain, and high efficiency.